2007
DOI: 10.1007/s00535-006-1924-9
|View full text |Cite
|
Sign up to set email alerts
|

Baseline gastric mucosal atrophy is a risk factor associated with the development of gastric cancer after Helicobacter pylori eradication therapy in patients with peptic ulcer diseases

Abstract: The grade of gastric atrophy was closely related to the development of gastric cancer after receiving H. pylori eradication therapy. Thus, eradication of H. pylori before the significant expansion of atrophy is most beneficial to prevent gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
133
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(137 citation statements)
references
References 33 publications
2
133
1
1
Order By: Relevance
“…The sex difference in gastric cancer patients was clearly demonstrated in previous epidemiological studies [37]. Several studies have also reported that severe gastric mucosal atrophy was a risk factor for MGC development [12,13,29]. Our group has previously demonstrated that inflammation triggered by H. pylori induced aberrant DNA methylation in gastric mucosae; the accumulation of such methylation was strongly associated with a risk of gastric cancer development (epigenetic field cancerization) [17][18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The sex difference in gastric cancer patients was clearly demonstrated in previous epidemiological studies [37]. Several studies have also reported that severe gastric mucosal atrophy was a risk factor for MGC development [12,13,29]. Our group has previously demonstrated that inflammation triggered by H. pylori induced aberrant DNA methylation in gastric mucosae; the accumulation of such methylation was strongly associated with a risk of gastric cancer development (epigenetic field cancerization) [17][18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 69%
“…Several studies have reported annual incidences of MGC after H. pylori eradication, ranging from 0.1 to 0.5 % in healthy individuals or peptic ulcer patients [26][27][28][29][30][31][32][33], and from 0.8 to 4.1 % in patients after endoscopic resection for early gastric cancer [9,[11][12][13][14][15]. Individuals after endoscopic resection had a higher risk of MGC compared with those who were healthy or had peptic ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 In addition, the number of subjects was small because the incidence of serologically diagnosed metaplastic gastritis is quite low, comprising <1% of the middle-aged Japanese population 31,32 and <20% of total gastric cancer cases. Considering the fact that H. pylori eradication does not completely eradicate cancer [7][8][9][10][11][12] and that eradication might be effective in the control of cancer development only among subjects with mild CAG, 7,10 posteradication subjects with extensive CAG and intestinal metaplasia should be considered another possible target for treatment with selective COX-2 inhibitors. However, special attention should be paid to recent evidence that long-term use of COX-2 inhibitors is associated with increased cardiovascular risk, including not only thrombotic events, but also hypertension, congestive heart failure, and arrhythmic events.…”
Section: Discussionmentioning
confidence: 99%
“…3 H. pylori eradication thus appears to be the most promising approach for the control of gastric cancer development, and the results of animal experiments have revealed that eradication of H. pylori, especially in the early stage, is effective for preventing stomach carcinogenesis. [4][5][6] However, current data indicate that H. pylori eradication does not lead to complete eradication of gastric cancer [7][8][9][10][11][12] and might be effective only in subjects without chronic atrophic gastritis (CAG) together with intestinal metaplasia. 7,10 Moreover, patients with extensive intestinal metaplasia-that is, metaplastic gastritis-should not be treated with eradication therapy, as bacterial load decreases with the progression of intestinal metaplasia, eventually resulting in spontaneous eradication.…”
mentioning
confidence: 99%
See 1 more Smart Citation